Ticagrelor Does Not Protect Against Endothelial Ischemia-Reperfusion Injury in Patients With Coronary Artery Disease. (May 2021) - Verouhis, Dinos; Ekström, Mattias; Settergren, Magnus; Sörensson, Peder; Pernow, John; Saleh, Nawzad
Background: Ticagrelor is a recommended P2Y12 receptor inhibitor after acute coronary syndrome (ACS). Its superiority has been suggested to rely on pleiotropic effects beyond platelet inhibition. Experimental studies indicate that ticagrelor may protect from ischemia-reperfusion injury but no data are available from such studies on patients. This study aimed to determine if chronic ticagrelor treatment protects against endothelial ischemia-reperfusion injury in patients with a previous ACS. Methods: Patients with a previous ACS were studied with flow mediated dilatation of the left brachial artery to determine the degree of endothelial ischemia-reperfusion injury before and after discontinuation of ticagrelor treatment, which had been continuous since 1 year. Each patient underwent 3 identical examinations. The first examination (Visit A) was at the end of ticagrelor treatment and the following 2 (Visit B and C) were after cessation of this treatment with an interval of 2 to 4 weeks. Results: Ischemia and reperfusion induced significant impairment of endothelial function at all 3 occasions (absolute decline in flow mediated dilatation 3.0% ± 0.7 at Visit A ( P < 0.001), 1.9% ± 0.9 at Visit B ( P < 0.05) and 1.9% ± 0.4 at Visit C ( P < 0.0001)). However, there was no difference in the degree of endothelial ischemia-reperfusion injury or baseline endothelial function between the visits. Conclusion: Chronic ticagrelor treatment in patients 1 year after an ACS does not protect against endothelial ischaemia-reperfusion injury. Nor is it associated with better basal endothelial function compared to after discontinuation of treatment.